Bone Morphogenetic Protein Antagonist Gremlin-1 Increases Myofibroblast Transition in Dermal Fibroblasts: Implications for Systemic Sclerosis - Duffy, Laura; Henderson, John; Brown, Max; Pryzborski, Stefan; Fullard, Nicola; Summa, Lena; Distler, Jorg H. W.; Stratton, Richard; O’Reilly, Steven (Frontiers in Cell and Developmental Biology, 2021)
Objective: Systemic Sclerosis is an autoimmune connective tissue disease which results in fibrosis of the skin and lungs. The disease is characterised by activation of myofibroblasts but what governs this is unknown. Gremlin-1 is a BMP antagonist that is developmentally regulated and we sought to investigate its role in SSc. Methods: Dermal fibroblasts were transfected with Grem1pcDNA3.1 expression vectors or empty vectors. Various markers of myofibroblasts were measured at the mRNA and protein levels. Scratch wound assays were also performed. Media Transfer experiments were performed to evaluate cytokine like effects. Various inhibitors of TGF-β signalling and MAPK signalling were used post transfection. siRNA to Gremlin-1 in SSc dermal fibroblasts were performed to evaluate the role of Gremlin-1. Different cytokines were incubated with fibroblasts and Gremlin-1 measured. Bleomycin was used as model of fibrosis and immunohistochemistry performed. Results: Overexpression of Gremlin-1 was achieved in primary dermal fibroblasts and lead to activation of quiescent cells to myofibroblasts indicated by collagen and α-Smooth muscle actin. Overexpression also led to functional effects. This was associated with increased TGF-β1 levels and SBE luciferase activity but not increased Thrombospondin-1 expression. Inhibition of Gremlin-1 overexpression cells with antibodies to TGF-β1 but not isotype controls led to reduced collagen and various TGF-β pathway chemical inhibitors also led to reduced collagen levels. In SSc cells siRNA mediated reduction of Gremlin-1 reduced collagen expression and CTGF gene and protein levels in these cells. IL-13 did not lead to elevated Gremlin-1 expression nor did IL-11. Gremlin-1 was elevated in an animal model of fibrosis compared to NaCl-treated mice. Conclusions: Gremlin-1 is a key regulator of myofibroblast transition leading to enhanced ECM deposition. Strategies that block Gremlin-1 maybe a possible therapeutic target in fibrotic diseases such as SSc.